PLGA-PLL-PEG-Tf-based targeted nanoparticles drug delivery system enhance antitumor efficacy via intrinsic apoptosis pathway - Bao W (Dove Medical Press, 2015)
Wen Bao,1 Ran Liu,1 Yonglu Wang,1,2 Fei Wang,1 Guohua Xia,1 Haijun Zhang,1 Xueming Li,2 Haixiang Yin,2 Baoan Chen11Department of Hematology and Oncology, Key Medical Disciplines of Jiangsu Province, Zhongda Hospital, Medical School of Southeast University, 2College of Pharmacy, Nanjing University of Technology, Nanjing, People’s Republic of ChinaAbstract: Chemotherapy offers a systemic cancer treatment; however, it is limited in clinical administration due to its serious side effects. In cancer medicine, the use of nanoparticles (NPs) drug delivery system (DDS) can sustainedly release anticancer drug at the specific site and reduce the incidence of toxicity in normal tissues. In the present study, we aimed to evaluate the benefit of a novel chemotherapeutic DDS and its underlying mechanisms. Daunorubicin (DNR) was loaded into poly (lactic-co-glycolic acid) (PLGA)-poly-l-lysine (PLL)-polyethylene glycol (PEG)-transferrin (Tf) NPs to construct DNR-PLGA-PLL-PEG-Tf-NPs (DNR-loaded NPs) as a DDS. After incubating with PLGA-PLL-PEG-Tf-NPs, DNR, and DNR-loaded NPs, the leukemia K562 cells were collected and the intracellular concentration of DNR was detected by flow cytometry, respectively. Furthermore, the effect of drugs on the growth of tumors in K562 xenografts was observed and the relevant toxicity of therapeutic drugs on organs was investigated in vivo. Meanwhile, cell apoptosis in the excised xenografts was measured by transferase-mediated dUTP nick-end labeling assay, and the expression of apoptosis-related proteins, including Bcl-2, Bax, Caspase-9, Caspase-3, and cleaved-PARP, was determined by Western blotting analysis. Results showed that DNR-loaded NPs increased intracellular concentration of DNR in K562 cells in vitro and induced a remarkable improvement in anticancer activity in the xenografts in vivo. The expression of Bcl-2 protein was downregulated and that of Bax, Caspase-9, Caspase-3, and cleaved-PARP proteins were obviously upregulated in the DNR-loaded NPs group than that in other ones. Interestingly, pathological assessment showed no apparent damage to the main organs. In summary, the results obtained from this study showed that the novel NPs DDS could improve the efficacy of DNR in the treatment of leukemia and induce apoptosis via intrinsic pathway. Thus, it can be inferred that the new drug delivery may be a useful clinical tool.Keywords: PLGA-PLL-PEG, daunorubicin, transferrin, K562 cells, apoptosis